Introducción a una poética y tres poemas representativos de Navaja de luciérnagas. - Campos López, Ronald (2012)
After my two poems books and this one, and my next one, a new paradigm has been confirmed: it's not personal is from a gruop together itself. Our perspective have been understood just a few times: poetry is the truth of the waken up souls.